From bench to bedside and to health policies (and back): ethics in translational research - Carlo Petrini (Istituto Superiore di Sanità, 2014)
INTRODUCTION: The medical aim of translational research is to smooth the transition of discoveries made through basic research from the laboratory bench to their diagnostic or therapeutic applications for patients. These applications may be extended to current clinical practice and to health policies. AIM: The converse is also important: health policies should provide a point of departure when identifying research priorities. Translational research poses the same ethical problems as trials with human subjects - albeit in different ways. One of the more significant problems is the risk for participants in trials: it is thus necessary to ensure that the risks to which these subjects are exposed are not out of proportion to the expected benefits. DISCUSSION: Translational research does not require new ethical principles, but existing biomedical principles need to be adjusted to the specific context. The well-being of participants should always be the primary objective; these persons should never be considered as means for the advancement of knowledge or for the improvement of applications.